Evaluation of acoustical parameters of a Brazilian popular housing model - Technical Notes - J. A. Ferreira; F. B. Diniz; A. Ferreira; P.H. T. Zannin (Archives of Acoustics, 2004)
The present survey shows the results obtained from the evaluation of the acoustical parameters in situ, through standardized measurements, inside a popular residence designed to offer an option to combat the housing deficit of the low income Brazilian population.